(untitled) - Bulugahapitiya , Vajira P. (Matara, 2013)
overing modern methods in organic synthesis, the fourth edition of this well-known textbook demonstrates their value, This book “Plant based natural products; extraction, isolation and phytochemical screening methods” provides the information about main classes of natural products, their extraction methods from plants material, separation or isolation methods of the compounds present in crude extracts and finally chemical screening methods to analysis the phytochemicals present in plant material
Keywords: Sản phẩm tự nhiên,Natural products.,Botanical chemistry.,Hóa học thực vật.,Medicinal plants,Cây dược liệu